Kajian Yuridis Tentang Upaya Hukum Peninjauan Kembali Dalam Sistem Hukum Pidana Di Indonesia - Suhaep Ashady; Nurdin Nurdin; Firzhal Arzhi Jiwantara (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Reconsideration legal action is an extraordinary legal effort against a court decision that has permanent legal force or that has execution power over a criminal case, in connection with the discovery of new facts or circumstances that will result in the release of the accused, these facts are commonly known as novum (new evidence). Reconsideration legal efforts according to the provisions of the Criminal Procedure Code are usually filed by the convict and his heirs. From this confirmation, the Public Prosecutor has no right to submit a Judicial Review because as is known, judicial review attempts aim to protect the interests of the convict. However, in several decisions the public prosecutor is allowed to file a judicial review. Therefore, this paper aims to legally examine who has the right to submit legal remedies for judicial review in criminal cases, both those that have been regulated in the Criminal Procedure Code and in practice. The research method used is normative legal research with a juridical approach, a conceptual approach supported by primary and secondary data sources. The results of the study show that even though the Criminal Procedure Code has clearly regulated who has the right to submit a judicial review, in practice the public prosecutor is allowed to submit a judicial review provided that an act being charged has been declared proven but not followed by a conviction. Therefore, this has created a polemic by ignoring existing regulations that have the potential to cause uncertainty in the implementation of the review so that the right to obtain legal certainty for the applicant for the review seems to have been violated.